KARAKTERISTIK EDIBLE FILM KOMPOSIT ALGINAT–MONTMORILLONIT - Amelya Setyawati; Giyatmi Giyatmi; Hari Eko Irianto; Dina Fransiska (Bajang Institute, 2026)
Alginate is the product of processing seaweed Sargassum sp. Alginate can be used as basic material in making edible film. The aim of the research is to find the effect of alginate an montmorillonite concentration to the characteristics of edible film (the moisture content, solubility, thickness, tensile strength, elongation, water vapor transmission rate, opacity measurement, and color). This study used a completely randomized design (CRD) pattern factorials by a Factor of A is the level alginate (1,00%; 1,25%; and 1,50%) and Factors B is the level montmorillonite (0,50%; 1,00%; and 1,50%) with 3 repetitions. The measured parameters were the moisture content, solubility, thickness, tensile strength, elongation, water vapor transmission rate, opacity measurement, and color. Based on the study on the characteristics of alginate-montmorillonite composite edible film it can be concluded that the best product based on chemical and mechanical test results is edible film made with 1.50% alginate concentration with 1.00% montmorillonite concentration resulting in a moisture content of 18.76%, solubility of 100%, thickness of 0.0368 mm, tensile strength of 32.27 MPa, percent of elongation of 47.66%, water vapor transmission rate of 12,04 g/m2/hours, opacity measurement of 3.23 YC / 2, L color test of 91.25, color test a equals -1.05, and color test b is 4.47. The montmorillonite concentration had no effect (P≥0.05) on the solubility value, and color test a is (greeness), but it had a very significant effect (P ≤0.01) on the value of thickness, percent elongation, water vapor transmission rate, and opacity value